Retoryka erotyzmu w prozie Milana Kundery - Skibska, Anna Maria (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2016)
In the essay, I make an attempt to explore a question of style, derived from Nietzsche’s discourse devoted to a figure of woman. Re-written subsequently by Derrida, the discourse itself turns out to be organized around the convoluted rhetoric events which are to reveal and at the same time conceal the representation of woman in both languages: of philosophy and of literature. As is well known, Kundera’s novels and essays consist in a significant and sometimes ambivalent confrontation occurring between these two languages, which also result in feminine characters’ construction often subordinated to the dominant rhetoric of eroticism. Furthermore, this rhetoric determines the dualistic perspective regarding the lovers’ relationships, according to which the image of woman is considered on different levels (i.e. as a reduction to the bodily ego, or emotional drive acting between sex and sublimation, etc.), which, however, always refer to the figurative procedure of transformation.
Keywords: rhetoric; eroticism; style; semiotic; symbolic; substitution